Current state on the development of nanoparticles for use against bacterial gastrointestinal pathogens: focus on chitosan nanoparticles loaded with phenolic compounds - Madureira, Ana Raquel (2016)
Gastrointestinal diseases have a huge impact especially in third world countries, making it urgent to seek new effective antimicrobial therapies. Thus, the development of nanoparticles (NPs) with bioactive compounds having antimicrobial activity has been the target of research over the past years. The development of antimicrobial drug NPs may be promising to overcome the problems associated with antibiotic resistance caused by many pathogenic bacteria. Moreover, the NPs administration of antimicrobial agents has advantages associated therewith, as use of low cost materials, contribution to the improvement of the therapeutic index and a controlled release drug by increasing the pharmacokinetics. These systems can be used to specific strains of bacteria, and to release interesting antimicrobial compounds. The phenolic compounds (PC) are a class of such bioactive compounds for which their antimicrobial activity was already tested on the production of NPs. Polymeric or lipidic NPs systems have been investigated to deliver these compounds. Chitosan is a polymer widely known for their properties, especially the antimicrobial activity and its ability to adhere to intestinal epithelium. This review article aims to evaluate and discuss recent developments in PC new delivery systems with antimicrobial activity against gastrointestinal pathogens, their production processes, activities, focusing on NPs produced using chitosan as the main structural and functional material.